FORMULASI TENTANG PERLINDUNGAN NEGARA TERHADAP ANAK YANG MELAKUKAN KEKERASAN DALAM RUMAH TANGGA (Studi Kasus di Pengadilan Negeri Medan) - Syaiful Asmi Hasibuan; Ediwarman Ediwarman; Marlina Marlina; Edy Ikhsan (USU LAW JOURNAL, 2016)
ABSTRACT Formulation of the goverment’s law abaut the children  protection Indonesian’s legislation home envisaged that more abstract nature protection or protection indirectly. In the criminal acts of the domestic violence committed by children, the judges tend to prioritize the protection of children as actors, so that the protection of victims is sometimes neglected. It can be seen from the judgment and consideration of the judge to look at the perpetrators are still categorized as a child. The court needs to provide the most appropriate sanctions in children who committed the crime. Giving or sentencing in the case of a child has an educational purpose in imposing sanctions. The criminal’s law policy on children whose commit domestic violence should consider the penal’s policies that include protection against the perpetrators and victims in the enforcement process is done in the criminal justice system. In addition, it should be also pay attention to non-penal’s policy which includes repairing the social conditions of children in the sense of legal protection which we put in harmony between perpetrators and victims of crimes that children are not only in juridical protection, but also in non-judicial protection. Keywords: State Protection, Child For Actors, Domestic Violence (domestic violence).